2022
DOI: 10.1038/s41467-022-31815-1
|View full text |Cite
|
Sign up to set email alerts
|

A SOX17-PDGFB signaling axis regulates aortic root development

Abstract: Developmental etiologies causing complex congenital aortic root abnormalities are unknown. Here we show that deletion of Sox17 in aortic root endothelium in mice causes underdeveloped aortic root leading to a bicuspid aortic valve due to the absence of non-coronary leaflet and mispositioned left coronary ostium. The respective defects are associated with reduced proliferation of non-coronary leaflet mesenchyme and aortic root smooth muscle derived from the second heart field cardiomyocytes. Mechanistically, SO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 111 publications
0
2
0
Order By: Relevance
“…The non‐coronary leaflet is derived from the intercalated leaflet swellings (sometimes called intercalated valve cushions); it has been proposed that it is a lack of these structures that results in the two‐sinus type of BAV (Anderson et al., 2014 ). Absence (or dysplasia) of the non‐coronary leaflet has been associated with SOX17‐PDGRB signalling (Lu et al., 2022 ). The other heart with BAV was seen in an E15.5 homozygote; the aortic valve appeared to be of the fused type, with the right and non‐coronary leaflets fused (Figure 3d ).…”
Section: Discussionmentioning
confidence: 99%
“…The non‐coronary leaflet is derived from the intercalated leaflet swellings (sometimes called intercalated valve cushions); it has been proposed that it is a lack of these structures that results in the two‐sinus type of BAV (Anderson et al., 2014 ). Absence (or dysplasia) of the non‐coronary leaflet has been associated with SOX17‐PDGRB signalling (Lu et al., 2022 ). The other heart with BAV was seen in an E15.5 homozygote; the aortic valve appeared to be of the fused type, with the right and non‐coronary leaflets fused (Figure 3d ).…”
Section: Discussionmentioning
confidence: 99%
“…Here, our scRNA-seq analysis revealed that Sox17 -null RT had reduced expression of several growth factor genes such as Tgfb2, Rspo1 , and Pdgfa , together with decreasing tendencies in Fgf and Wnt family ligands. Tgfb2 and Pdgfa are known to be involved in valve formation of the heat and aorta 45 , 46 , while they can contribute to the activation of PI3K-AKT signaling 47 , 48 which is characteristic of the SV Sertoli cells. Similarly, FGF9 activates AKT in Sertoli cells 25 .…”
Section: Discussionmentioning
confidence: 99%